METAFUNGSI BAHASA DALAM EPISODE “ASYIKNYA BERKEMAH” PADA KARTUN ADIT SOPO JARWO: KAJIAN SFL HALLIDAY - Della Eka Putri; Sumarti Sumarti; Mulyanto Widodo; I wayan Ardi Sumarta (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze language metafunctions in the camping-related conversations in the cartoon Adit Sopo Jarwo using Halliday’s Systemic Functional Linguistics (SFL) approach. This research employs a descriptive qualitative method with documentation techniques through conversation transcripts consisting of 45 clauses from three contexts. The data were analyzed based on three language metafunctions, namely ideational, interpersonal, and textual metafunctions. The findings show that the ideational metafunction is dominated by material processes that represent the characters’ physical activities, accompanied by mental and relational processes that express attitudes and conditions of participants. In the interpersonal metafunction, declarative clauses with modality are predominantly used to build social interaction while conveying information. Meanwhile, the textual metafunction reveals a coherent and structured Theme-Rheme pattern that organizes the flow of information. The novelty of this study lies in the use of conversational data from an Indonesian local cartoon as the object of metafunction analysis, which has mostly been applied to written texts or formal discourse, thus contributing to SFL studies in popular media and informal interaction. The implication of this study is that the metafunctions of language can be applied to popular media such as cartoons to understand interaction patterns and language functions in informal communication.